Study of ion bombardment of SiC ceramics: Surface and interfacial reaction modification. Issue 4 (April 2020) - Chen, Z.B.; Hu, S.P.; Duan, X.K.; Dan, M.; Song, X.G.; Long, W.M.; Feng, J.C.
Highlights: Surface modification of SiC ceramics induced by Ar ion bombardment was investigated. An amorphous layer was formed at SiC surface after ion bombardment for fluence of 1 × 10 17 ions/cm 2 at 50 keV. Beneath the amorphous layer, high-density dislocations and twin crystals were formed by ion bombardment. Ion bombardment improved bonding quality of ceramics/filler interface effectively, and no reactant stratification occurred. The shear strength of SiC brazed joints was improved with Ar ion bombardment. Abstract: Ar ion bombardment was conducted to modify the SiC surface microstructures, which had a vital effect on the interfacial microstructure and shear property of brazing joints. The amorphous layer with thickness of ∼120 nm was formed on the bombarded surface, accompanied with plenty of dislocations and twins beneath the amorphous layer. Reliable SiC/AgCu-Ti/SiC joints were brazed in vacuum at 900 °C for 10 min, and the interfacial microstructure was investigated by SEM, EDS and TEM in detail. When the ion bombarded SiC was used as substrates, the microstructure of brazing beam was optimized as SiC / Ti5 Si3 + TiC mixed layer / Ag(s, s) + Cu(s, s) containing TiCu / Ti5 Si3 + TiC mixed layer / SiC, in which the interfacial stratification was eliminated compared to the conventional SiC brazing. The shear strength was improved to 30.9 MPa with ion bombardment, which was ∼72.6 % higher than that of the original SiC joints without ion bombardment. The proposed Ar ion bombardment method provides a novel way to modify the brazability of ceramics.